Judy Moody predicts the future - McDonald, Megan; Reynolds, Peter, 1961-; Walker Books (London : Walker Books, 2006)
After Judy obtains a mood ring, she tries to convince herself and her third-grade classmates that she can predict the future.
3.1
3-6
Keywords: Moody, Judy (Fictitious character) -- Juvenile fiction; Prophecies -- Juvenile fiction; Rings -- Juvenile fiction; Schools -- Juvenile fiction; Moody, Judy (Fictitious character) -- Fiction; Prophecies -- Fiction; Rings -- Fiction; Schools -- Fiction; Moody, Judy (Fictional character) -- Fiction; School stories